2009
DOI: 10.1097/qai.0b013e31818d5a27
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure Antiretroviral Prophylaxis Attitudes in High-Risk Boston Area Men Who Report Having Sex With Men: Limited Knowledge and Experience but Potential for Increased Utilization After Education

Abstract: Background Pre-exposure prophylaxis (PrEP) could protect individuals engaging in repeated high-risk behaviors from HIV infection. Understanding the demographic and behavioral predictors of intent to use PrEP may prove useful to identify clinical trial participants. Methods In 2007, 227 HIV-uninfected MSM recruited through modified respondent-driven sampling completed an interviewer-administered survey assessing prior PrEP use and awareness, future intent to use PrEP, demographics, sexual risk, psychosocial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
171
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(213 citation statements)
references
References 25 publications
22
171
12
Order By: Relevance
“…Participants reported low levels of knowledge and discussion about PrEP in the community, which may have hindered their ability to speak to others about their PrEP use; this observation is consistent with others made at the time, regarding community knowledge of PrEP. [45][46][47] A few participants reported concerns about being seen with pills that may be associated with HIV, although stigma seems to be a much greater barrier to adherence in other studies and at other sites. 25,27,48 Future strategies to support MSM in discussing their participation in PrEP studies/implementation programs and their overall pill taking could include peer support interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported low levels of knowledge and discussion about PrEP in the community, which may have hindered their ability to speak to others about their PrEP use; this observation is consistent with others made at the time, regarding community knowledge of PrEP. [45][46][47] A few participants reported concerns about being seen with pills that may be associated with HIV, although stigma seems to be a much greater barrier to adherence in other studies and at other sites. 25,27,48 Future strategies to support MSM in discussing their participation in PrEP studies/implementation programs and their overall pill taking could include peer support interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Congruent with other studies, participants indicated that many persons who would benefit from PrEP report interest in it (Krakower et al, 2012;Mimiaga, Case, Johnson, Safren, & Mayer, 2009;Mustanski, Johnson, Garofalo, Ryan, & Birkett, 2013) but are unware of how the medication works and how it is part of an overall HIV prevention strategy (Knight et al, 2016). PrEP awareness, or lack thereof, among participants is representative of an underdeveloped sexuality education system to serve MSM and other sexual minorities in relatively rural states (Kubicek, Beyer, Weiss, Iverson, & Kipke, 2010;Poon & Saewyc, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Findings show significant associations of barebacking identity to serodiscordant unprotected insertive anal sex and suggest that encouraging harm-reduction strategies, in particular strategic positioning, may be an appropriate intervention technique to employ with self-identified barebacking MSM who may not respond to the prevention goal of completely eliminating unsafe sex. 12 Moreover, preceding studies have documented willingness to use rectal microbicides, 37,38 and postexposure prophylaxis (PEP) or pre-exposure prophylaxis (PrEP) [39][40][41] among HIV seronegative MSM. Recent research has begun to explore the acceptability of alternative HIV biomedical products (microbicides, vaccines, PEP, and PrEP) with MSM who engage in unsafe sex.…”
Section: Discussionmentioning
confidence: 99%